2009
DOI: 10.1152/ajprenal.90309.2008
|View full text |Cite
|
Sign up to set email alerts
|

Low-vitamin E diet exacerbates calcium oxalate crystal formation via enhanced oxidative stress in rat hyperoxaluric kidney

Abstract: Huang HS, Ma MC, Chen J. Low-vitamin E diet exacerbates calcium oxalate crystal formation via enhanced oxidative stress in rat hyperoxaluric kidney. Am J Physiol Renal Physiol 295: F34-F45, 2008. First published September 17, 2008 doi:10.1152/ajprenal.90309.2008.-Vitamin E was previously reported to reduce calcium oxalate (CaOx) crystal formation. This study explored whether vitamin E deficiency affects intrarenal oxidative stress and accelerates crystal deposition in hyperoxaluria. The control (C) group of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 28 publications
4
31
0
Order By: Relevance
“…Histopathological studies showed interstitial inflammation and high CaOx crystal deposition in the kidneys of rats fed with KOx diet. This result is concordant with previous study by Huang, Ma, and Chen (2009) who reported that oxidative stress and renal injury are associated with CaOx crystal deposition in hyperoxaluric rats, which is a crucial factor in crystal retention and subsequent stone formation. LAB administered rats showed normal morphology of renal tissue and decreased crystal deposition compared to rats fed with KOx.…”
Section: Discussionsupporting
confidence: 93%
“…Histopathological studies showed interstitial inflammation and high CaOx crystal deposition in the kidneys of rats fed with KOx diet. This result is concordant with previous study by Huang, Ma, and Chen (2009) who reported that oxidative stress and renal injury are associated with CaOx crystal deposition in hyperoxaluric rats, which is a crucial factor in crystal retention and subsequent stone formation. LAB administered rats showed normal morphology of renal tissue and decreased crystal deposition compared to rats fed with KOx.…”
Section: Discussionsupporting
confidence: 93%
“…Multifactorial conditions including oxalate-induced free radical production cause damaged tubular epithelial cells [11] which subsequently induce crystal deposition and stone formation [9]. Several studies also reported that crystal and stone can aggravate oxidative stress as well [8, 9, 12, 25, 27]. According to this, oxidative stress appears to be a vicious cycle for urolithiasis.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have provided a more focused correlation between the oxalate-induced production of free radicals and effects of vitamin E. In rats fed with a vitamin E-defi cient diet accompanied by EG treatment, the formation of CaOx crystals intensified and their volume in urinary sediment increased causing atrophy and dilatation of tubules as well as interstitial cellular infi ltration. The administration of vitamin E ameliorated these effects, most likely due to its anti-oxidative properties (74,75). Vitamin B6 defi ciency increased the excretion of endogenous oxalate, which was further enhanced by adding glycine, deoxypyridoxine, and isonicotic acid hydrazide to the diet (76).…”
Section: Compounds and Other Factors That Modulate Urine Oxalate Concmentioning
confidence: 99%